Oral health habits, prevalence of dental caries and dental erosion in adolescents - COSTA,Fernanda Clotilde Mariz da (2017)
ABSTRACT Objective To assess oral hygiene habits, and prevalence of dental caries and erosion in adolescents of Campina Grande, Paraíba, Brazil. Methods Cross-sectional study with random cluster sampling involving 201 15-year-old schoolchildren. Oral health habits were obtained through questionnaire, and socioeconomic data, by means of interviews. The DMFT index was adopted to determine the prevalence of caries and that proposed by O’Sullivan, to assess dental erosion. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 18. A 5% significance level was adopted. Results All subjects reported using toothbrush and toothpaste, 50.7% reported dental flossing, and association was found between sex and use of mouthwash (p <0.05). Regarding dental caries, the mean DMFT was 3.67 and 51.7% had DMFT lower than or equal to 3. For dental erosion, 18.4% of the sample had erosive lesions, predominantly enamel lesions (92%). Conclusion The use of dental floss was low and adolescents revealed unsatisfactory index. The DMF-T value was moderate and lower than that reported for the Brazilian age group. The prevalence of dental erosion was high, with predominance of enamel lesions.